2017
DOI: 10.1159/000467940
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Fastigial Nucleus Electrical Stimulation Alleviates Depressive-Like Behaviors in Post-Stroke Depression Rat Model and Potential Mechanisms

Abstract: Objective: To identify the molecular mechanism of post-stroke depression (PSD), and observe the therapeutic effects of cerebellar fastigial nucleus electrical stimulation (FNS) on the behaviors and regional cerebral blood flow (rCBF) in a PSD rat model. Methods: Healthy SD rats were randomly divided into four groups (sham, stroke, post-stroke depress and FNS group). Sham group (n = 6) underwent sham operation. The other three groups (n = 6*3) underwent MCAO. Rats were examined twice a week in open filed test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…To study whether MCAO model induces cognitive impairment as reported and HSYA has a protective effect on cognitive impairment induced by cerebral ischemia reperfusion, we first carried out a serious behavioral experiment. Using the open field test, we found brain ischemia induced by MCAO did not influence spontaneous locomotor activities on the rats which was consistent with previous study (Chang et al, 2016 ; Zhang et al, 2017 ). However, Katsuta et al ( 2003 ) showed that global ischemia induced in gerbils produced a significant increase in locomotor activity and administration of neuroprotective agents ameliorated locomotor hyperactivity.…”
Section: Discussionsupporting
confidence: 92%
“…To study whether MCAO model induces cognitive impairment as reported and HSYA has a protective effect on cognitive impairment induced by cerebral ischemia reperfusion, we first carried out a serious behavioral experiment. Using the open field test, we found brain ischemia induced by MCAO did not influence spontaneous locomotor activities on the rats which was consistent with previous study (Chang et al, 2016 ; Zhang et al, 2017 ). However, Katsuta et al ( 2003 ) showed that global ischemia induced in gerbils produced a significant increase in locomotor activity and administration of neuroprotective agents ameliorated locomotor hyperactivity.…”
Section: Discussionsupporting
confidence: 92%
“…After stroke, much of patients suffered motor impairment, which limit their mobility, lost confidence, which may lead to PSD [32]. The previous studies had proven the positive effects of PEMS on motor function [25,26],animal experiments showed that FNS alone or in combination with drug therapy could improve PSD [33],while in clinical practice, the effect of PMES on PSD was unclear. Hence, in the present study, we investigated the effect of PMES on PSD assessed by HRDS, and we found that PMES combined with antidepressant had been significantly more successful in improving poststroke depression than medication alone.…”
Section: Discussionmentioning
confidence: 99%
“…In previous animal studies, it was found that FNS could up-regulated noradrenaline (NE) and 5-HT in the frontal lobe of depressed rats [19,20]. Recent clinical studies have shown that FNS alone or in combination with drug therapy can improve PSD [21]. Fan et al found that the cognitive function decreased on 2 months after chronic cerebral hypoperfusion, and was worse on 4 months after hypoperfusion, the cognitive function improved after FNS treatment [10].…”
Section: Discussionmentioning
confidence: 99%